Characterization and electrochemical properties of graphite felt-based electrode modified using an ionomer impregnation approach for vanadium redox flow battery. (10th October 2017) - Chou, Yi-Sin; Jeng, King-Tsai; Yen, Shi-Chern
Graphical abstract: Highlights: Modification of graphite felt electrode is conducted by ionomer impregnation. The modified GF electrode produces distinct CV with pronounced redox signals. Applied electric field might have caused surface graphitization of GF electrode. The VRFB with modified electrodes exhibits an excellent cell performance. Redox reactions occur at the graphitic sites not via surface functional groups. Abstract: Vanadium redox flow battery (VRFB) is a promising electrical energy storage device, particularly for applications with intermittent-type renewable energies. In practical operation, the commonly used graphite felt (GF)-based electrode has to be modified first to generate a hydrophilic environment suitable for redox reactions of vanadium ions to proceed. This study proposes a novel modification approach by impregnation with a Nafion ® ionomer solution that significantly improves the wettability and substantially enhances the activity of the GF electrode. Characterizations of modified electrode are carried out using various techniques. The whole-cell cyclic voltammogram obtained is well-defined having a wider electrochemical window and more pronounced redox signals than those of the electrochemically oxidized counterpart. Characterization results indicate that there are no surface functional groups generated other than the sulfonic acid of the coated ionomer, and the applied electric field might have caused improved surface graphitization of the modified GF electrode. Electrochemical test results suggest that the electrode kinetics follows a diffusion-controlled process with simple electron transfer redox reactions proceeding directly through the surface graphitic sites, instead of via generated surface functional groups as the conventionally recognized paradigm. Moreover, the fabricated single-cell VRFB exhibits an excellent cell performance. The related redox reaction mechanisms are proposed.